Ivabradine increases the high frequency gain ratio in the vagal heart rate transfer function via an interaction with muscarinic potassium channels. Issue 23 (9th December 2021) - Kawada, Toru; Yamamoto, Hiromi; Miyamoto, Tadayoshi; Hayama, Yohsuke; Li, Meihua; Zheng, Can; Uemura, Kazunori; Sugimachi, Masaru; Saku, Keita
Abstract: Muscarinic potassium channels ( I K, ACh ) are thought to contribute to the high frequency (HF) dynamic heart rate (HR) response to vagal nerve stimulation (VNS) because they act faster than the pathway mediated by hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels. However, the interactions between the two pathways have not yet been fully elucidated. We previously demonstrated that HCN channel blockade by ivabradine (IVA) increased the HF gain ratio of the transfer function from VNS to HR. To test the hypothesis that IVA increases the HF gain ratio via an interaction with I K, ACh, we examined the dynamic HR response to VNS under conditions of control (CNT), I K, ACh blockade by tertiapin‐Q (TQ, 50 nM/kg), and TQ plus IVA (2 mg/kg) (TQ + IVA) in anesthetized rats ( n  = 8). In each condition, the right vagal nerve was stimulated for 10 min with binary white noise signals between 0–10, 0–20, and 0–40 Hz. On multiple regression analysis, the HF gain ratio positively correlated with the VNS rate with a coefficient of 1.691 ± 0.151 (×0.01) ( p  < 0.001). TQ had a negative effect on the HF gain ratio with a coefficient of −1.170 ± 0.214 (×0.01) ( p  < 0.001). IVA did not significantly increase the HF gain ratio in the presence of TQ. The HF gain ratio remained low under the TQ + IVA condition compared to controls. These results affirm that the IVA‐induced increase in the HF gain ratio is dependent on the untethering of the hyperpolarizing effect of I K, ACh . Abstract : The interactions between two major mechanisms of vagal heart rate (HR) control, namely, the muscarinic potassium channel ( I K, ACh ) pathway and the hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channel pathway, need to be fully elucidated. Blockade of HCN channels by ivabradine (IVA) reduces HR and increases the high frequency (HF) gain ratio of the transfer function from vagal nerve stimulation to HR in our previous studies. Under I K, ACh blockade, IVA did not increase the HF gain ratio compared to controls in the present study. The IVA‐induced increase in the HF gain ratio is dependent on the untethering of the hyperpolarizing effect of I K, ACh .